MEMBANGUN LOYALITAS PELANGGAN : STUDI TERHADAP KUALITAS LAYANAN, HARGA, DAN KEPUASAN DI PT. J & T EKSPRESS BANGKINANG - Putri, Librina Tria; Setiawan, Adi; Salis, Muhammad; Ali , Auzar (Komunitas Manajemen Kompetitif, 2024)
Abstract This study aims to determine the effect of service quality, price and customer satisfaction simultaneously and partially on customer loyalty (survey at PT. J&T Ekspress Bangkinang Branch). The sampling technique used is by using simple random sampling method, which means taking samples from members of the population randomly without regard to strata. So to determine the sample, the Slovin formula is used with a total sample of 100 customers. Data analysis technique using multiple linear regression models. The results of hypothesis testing simultaneously and partially show that the variables of service quality, price and customer satisfaction have a significant effect on customer loyalty at PT. J&T Express Bangkinang Branch. The closeness of the relationship between the variables of Service Quality, Price and Customer Satisfaction with Loyalty at PT. J&T Express Bangkinang Branch of 88.1% with a high contribution level, while the remaining 11.9% is influenced by other variables. Keywords Customer Loyalty, Customer Quality, Price dam Consumer Satisfaction